Fetal Intracranial Hemorrhage (Fetal Stroke): Report of Four Antenatally Diagnosed Casesand Review of the Literature - Ying-Fen Huang; Wei-Chih Chen; Jenn-Jhy Tseng; Esther Shih-Chu Ho; Min-Min Chou (Elsevier, 2006)
Objective: Neonatal intracranial hemorrhage (ICH) has been estimated to be high in premature infants, occurring in approximately 40% of infants of less than 32 weeks' gestation. However, the true incidence of ICH in utero has not been determined. We present our experience with four cases of fetal ICH (fetal stroke), which was detected prenatally by ultrasonography (US). Materials and Methods: Four cases of fetal ICH were identified over a 2-year period at the prenatal unit of Taichung Veterans General Hospital, Taiwan. Prenatal and neonatal sonograms, computed tomography (CT) scan or magnetic resonance imaging (MRI), medical records, and the clinical course were assessed retrospectively. In each case, a series of initial and follow-up obstetric sonograms were available. Fetal stroke was recognized by several sonographic features: irregular echogenic brain mass, intraventricular echogenic foci or periventricular echodensities; ventriculomegaly; and posthemorrhagic hydrocephalus (PHH). A detailed investigation for possible etiology of fetal ICH was performed in all cases. Results: Transabdominal US showed hyperechoic lesions in the lateral ventricle and ventriculomegaly in three of the four fetuses, and a massive intraparenchymal hemorrhage in the remaining one. Three fetuses were born vaginally and one by cesarean section due to an enlarged head circumference. Abnormal nonstress tests and abnormal flow velocity waveforms in the umbilical and middle cerebral arteries were present in two cases. Intrapartum fetal death and neonatal death occurred in the first two cases associated with maternal preeclampsia at 31 and 27 weeks, respectively. In the remaining two infants, the one in case 3 underwent ventriculoperitoneal shunting, which developed normally at the age of 18 months. The other infant in case 4 had PHH after suspicious choroids plexus hemorrhage, and the detailed information regarding the cause of neonatal death was not available. Conclusion: This small series demonstrate that an antenatal diagnosis of fetal stroke with intraventricular hemorrhage Grades III and IV or with brain parenchymal involvement appears to be associated with poor neurologic outcome. Due to the significant neonatal neurologic impairment and potential medicolegal implications of antepartum fetal ICH, it follows that obstetricians and sonographers should be familiar with predisposing factors and typical diagnostic imaging findings of rare in utero ICH events.